Fashion parades – for men only: Multiple tailor Hepworths, designer Hardy Amies and the marketing of men's suits in Britain in the 1960s. Issue 1 (1st September 2019) - Sprecher, Danielle
This article will examine the use of male fashion shows as a marketing and promotional tool by British high street multiple tailor Hepworths in the 1960s as part of their design collaboration with women's fashion designer and couturier Hardy Amies. The partnership successfully brought the concept of the branded designer label to British men for the first time and was a major initiative for the menswear industry as it highlighted and consolidated a design ethos which strongly emphasized men's fashion. Drawing on a wide range of primary source material including oral history interviews with two male models who worked for Hepworths and Amies; object studies of surviving garments; and film and images of the shows, this article will explore the significant and innovative approach to selling men's fashionable tailoring taken by this mid-market menswear company. It also provides a broader understanding of the history of men's fashion during this period, a narrative which is dominated by the concept of the peacock revolution, by demonstrating Hepworths' important contribution to everyday men's fashion in post-Second World War Britain.